What do expectant parents know about antenatal ultrasound screening? - ESİM BÜYÜKBAYRAK, ESRA; ANIK İLHAN, GÖKÇE; SOYSAL, SUAH (TAYLOR & FRANCIS LTD, 2020)
Objective: We aimed to investigate and compare the background knowledge and attitudes of pregnant women and their partners about antenatal ultrasound scans. Materials and methods: A cross-sectional survey was conducted in a university perinatology clinic. Pregnant women and their partners who underwent the first trimester ultrasound scan or the second trimester anomaly scan were invited to complete a questionnaire which contained items on their sociodemographic characteristics, knowledge, and attitude. Results: In total, 500 eligible expectant mothers and their partners (220 in the first trimester and 280 in the second trimester) were recruited. The knowledge and attitude of expectant mothers and fathers were statistically similar. Working status, education level, and presence of chronic disease were the factors affecting the number of correct answers in both expectant mothers and fathers. The knowledge levels of both the expectant mothers and fathers were similar in the first and second trimesters. Conclusions: Pregnant women's and their partners' attitudes and knowledge on antenatal ultrasound scans were similar and generally satisfactory.
Keywords: Attitude; expectant father; expectant mother; knowledge; ultrasound; EXPERIENCES; KNOWLEDGE; 1ST-TRIMESTER; WOMEN; WANT